2014
DOI: 10.1186/s13028-014-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of gastrointestinal parasites in reptiles: comparison of two coprological methods

Abstract: BackgroundExotic reptiles have become increasingly common domestic pets worldwide and are well known to be carriers of different parasites including some with zoonotic potential. The need of accurate diagnosis of gastrointestinal endoparasite infections in domestic reptiles is therefore essential, not only for the well-being of captive reptiles but also for the owners. Here, two different approaches for the detection of parasite stages in reptile faeces were compared: a combination of native and iodine stained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 35 publications
1
32
1
5
Order By: Relevance
“…Parasites may have detrimental effects on the well-being of reptiles kept in zoos, farms or as domestic pets [4,5]. The different techniques were used for detection of parasitic ova in feces of snakes as per previous researchers [9][10][11][12]. For the identification of nematode eggs and protozoan oocysts, fecal floatation was found superior to other methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasites may have detrimental effects on the well-being of reptiles kept in zoos, farms or as domestic pets [4,5]. The different techniques were used for detection of parasitic ova in feces of snakes as per previous researchers [9][10][11][12]. For the identification of nematode eggs and protozoan oocysts, fecal floatation was found superior to other methods.…”
Section: Discussionmentioning
confidence: 99%
“…Direct smear, flotation and sedimentation techniques were used for fecal examination as per standard procedure [9][10][11][12]. Fecal samples of dead snakes were examined during post mortem examination.…”
Section: Collection and Examination Of Fecal Samplesmentioning
confidence: 99%
“…Lizards were reported as hosts for more oxyurid species of the family Pharyngonidae (Greiner & Mader, 2006), but it was impossible to identify those species based only on the measurements and morphological features of eggs. Although recent studies (Wolf et al 2014) have shown that the use of flotation technique (CNF) allows differentiation of lizard species versus rodent species oxyurid eggs (Aspiculuris/Syphacia, e.g. in monitor lizard).…”
Section: Discussionmentioning
confidence: 99%
“…These fi ndings confi rm data from stool survey, indicating that infections with more than one species of helminth may be common in L. miliaris, even under natural conditions. Since there is a defi cit in knowledge about the prevalence of parasites from snakes in nature, the observation of high percentages of occurrence of helminths in L. miliaris becomes more relevant, especially given the fact that most of the parasitological surveys in reptiles refer to captive animals, for which prevalence rates in stool samples may vary greatly due to the conditions of confi nement and/or periodic deworming (Rataj et al, 2011;Okulewicz et al, 2014;Wolf et al, 2014). Table 1 shows that a large number of species of helminths have L. miliaris as their host.…”
Section: Strongyloides Ophidiaementioning
confidence: 99%